GAS DRYER DESIGN FOR VERMICELLI USING MICROCONTROLLER ATMEGA 8535 - Akhmad Mufasil; Ida Betanursanti (Spektrum Industri, 2013)
The purpose of this research is designing a gas dryer for vermicelli using a microcontroller ATmega 8535 that can overcome the obstacles in the drying department. The microcontroller ATmega 8535 used to regulate the temperature of the drying chamber. This tool design is made to compare between conventional dryer and a theoritical gas dryer in the factory. The method used in this paper is field study in the factory. Based on the experience then theoritical gas dryer design from the factoryâ€™s datas. A microcontroller Atmega 8535 is added to the dryer to easier the dryer operation. The result of the theoritical gas dryer design for vermicelli using a microcontroller ATmega 8535, showed a faster time drying for 131,04 kg of vermicelli need 47,72 minutes at a temperature of 40- 55Â° C. Keywords: Gas dryer, vermicelli and microcontroller ATmega 8535.